L2 Turkish Curriculum Development in the Republic of Cyprus: Evaluation and Improvement - Mavrommati, Spyroula (Language Center, Cyprus University of Technology, 2021)
This dissertation examines the area of teaching and learning Turkish as a second language (L2), at an A1 Common European Framework of Reference for Languages (CEFR) level, in a private institute in the Republic of Cyprus (RoC), with a focus on the evaluation and improvement of L2 Turkish Curriculum. The first aim is to provide a critical examination of existing curriculum materials for the teaching and learning of Turkish as an L2 in the RoC. This includes the examination of one set of materials, ISTANBUL A1, published in 2015 (Aslan) and used for the teaching of Turkish in this context, taught at a specific private institute. The descriptive evaluation is based on L2 curriculum evaluation criteria, which derive from current theories and practices in L2 curriculum development evaluation. The second aim of this dissertation, which is based on the findings of the curriculum evaluation, is to investigate current theories and practices in L2 curriculum development, and improve the curriculum for adults in this particular, and give evaluative insights into the planning and implementation stages. The Moodle platform was used to create an online learning environment and facilitate interactive learning. An improved Turkish language learning curriculum, based on current theories and practices in L2 was uploaded and accessible on this platform. The study was based on Action Research (AR). The data collected were analysed through quantitative and qualitative methods. The findings revealed that the existing material in the teaching and learning of Turkish as an L2 in the RoC to a specific private institute’s group of adult learners is not compatible with current theory and practice in L2 curriculum development. Hence, a socially constructed curriculum based on current theories and practices in L2 was designed and piloted. The results proved that through this there is growth in learners’ confidence and retention of knowledge with the use of socially constructed curriculum.
Keywords: L2 Curriculum evaluation and improvement; Turkish as an L2; Adult Learners; Socially Constructivist Curriculum; Online L2 Learning; Social Constructivism learning theory; Communicative Language Teaching